Macroeconomic foundations of macroeconomics - Cencini, Alvaro (Routledge frontiers of political economy, 2005)
Contrary to common belief, macroeconomics is not merely a theory of aggregates, and cannot be constructed from individual behaviour. Both nationally and internationally, there are economic laws that are logically independent of economic agents' behaviour. These are the macroeconomic foundations of macroeconomics. Presenting cutting-edge material, Alvaro Cencini explores these foundations, and shows that the introduction of money entails economics being interpreted conceptually not mathematically. His innovative book provides the elements for a new approach by applying the most.